(untitled) (Bangladesh Journal of Pharmacology, 2014)
Malva parviflora (cheeseweed) is traditionally used as hepatoprotective. The current study was conducted to determine its hepatoprotective activity of aqueous methanolic extract of whole plant. Two doses of plant (250 mg/kg and 500 mg/kg) were administered in paracetamol intoxicated mice and results were compared with silymarin. Observational parameters were ALT, AST, ALP and total bilirubin. The results showed that the extract of M. parviflora produced significant (p<0.001) reduction in liver enzymes and total bilirubin. Results were supported by histopathological investigation, phytochemical screening and detection of hepatoprotective constituents (kaempferol and apigenin) by HPLC. So, the current study showed that aqueous methanolic extract of M. parviflora possesses hepatoprotective activity.